Colonial textile culture in mid-nineteenth century Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in History at Massey University, Manawatū, New Zealand - McKergow, Fiona Mary (Massey University, 2020)
Historians are increasingly paying attention to the intersections between objects, people and places as an aspect of the social and cultural histories of settler colonial societies. This thesis investigates selected textiles of British migrant and settler women in Aotearoa New Zealand as an element of what is defined here as ‘colonial textile culture’. It draws on the collections of mid-nineteenth century clothing and textiles held at two provincial museums in the lower North Island of New Zealand: Te Manawa Museum of Art, Science and History, in Palmerston North, and Whanganui Regional Museum, in Whanganui. Colonial textile culture is examined through six surviving objects associated with migrant women of English, Irish and Scottish ethnic origin. These are presented as part of a wider re-evaluation of textiles in colonial cultural history. A set of journals, a mourning sampler and a workbox allow insights into the more personal aspects of textile culture, while a silk wedding dress, a battle flag and a straw bonnet reflect its more public dimensions. Many of these are revealed to be highly emotional objects, in addition to their sensory dimensions, that were essential to the making of relationships, identities and experiences. The concept of colonial textile culture encapsulates the ways in which textiles in mid-nineteenth century Aotearoa New Zealand variously created and sustained family memories; contested and reinforced notions of social class; related to both feminine and masculine identities; and served as a site of interaction between British migrant and settler women and Māori communities. Colonial textile culture was also a source of commercial opportunity for some women. Finally, it was part of a wider circulation of commodities, ideas and practices throughout the British Empire that provided an underpinning to the extension of settler colonialism.
Listed in 2020 Dean's List of Exceptional Theses
Keywords: Textile fabrics; Material culture; Clothing and dress; New Zealand; History; 19th century; Social life and customs; Social conditions; Dean's List of Exceptional Theses; 430320 New Zealand history; 430206 Heritage collections and interpretations